Pengaruh Penerapan Indonesia-Japan Economy Partnership Agreement (IJEPA) Terhadap Peningkatan Investasi Sektor Industri Manufaktur Jepang Di Indonesia Tahun 2008-2018 - Ahmad Maulana Nur Hidayat; Andi Purwono (Faculty of Social and Political Sciences - Universitas Wahid Hasyim, 2021)
The superiority of different resources in each country has triggered the emergence of interdependence and cooperation in various fields, one of which is Economics and Investment. Indonesia-Japan bilateral relations in the field of Economy and Investment have lasted more than 60 years and reached a peak during the agreement of the Indonesia Japan Economy Partnership Agreement (IJEPA) in 2008. After the implementation of Japanese investment IJEPA in Indonesia which had dropped during the Asian crisis hit in 1997 -1998 increased significantly with the largest portion of the increase in the Manufacturing Industry sector in the period 2008 - 2018.